Identidade e território da Associação Quilombola Urbana Jardim Cascata - Aparecida de Goiânia(1988-2015) - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
The process of urban space production are marked by different dynamics, which intersect and define from the trajectories and socio-spatial narratives. From this perspective, we point out that the city is configured as a plural space in which they are established also as plural territories. Among this diversity of urban areas, we established as spatial area to study those promoted by the Urban Quilombo Cascade Garden Association (AQUJC), an organization that brings together social subjects that attributed themselves Maroons. Thus, our main goal is to analyze the spatial and temporal experiences of these subjects and their space production processes. For this, we used two categories of analysis: because it is a quilombo association, the identity category was vitally important to understand the motivations that lead its members to allocate themselves as quilombos; and, because it is an entity that has political and social achievements that directly reflect on the creation of spaces, the territory category helps us understand the socio-spatial dynamics promoted by the action of AQUJC. To develop this study we use the methodology of participant research, by this, it was made field observations, semi-structured interviews and questionnaires. The research tracks, therefore the socio-spatial and identity dynamics of Quilombolas from Cascade Garden, analyzing their particular identity and their territory constitution processes.
Keywords: Associação Quilombola Urbana Jardim Cascata; Identidade; Território; Comunidade; Casas Quilombolas; Urban Quilombo Cascade Garden Association; Identity; Territory; Community; Quilombolas homes; CIENCIAS HUMANAS::GEOGRAFIA; CIENCIAS HUMANAS::ANTROPOLOGIA; CIENCIAS HUMANAS::HISTORIA